A Multifunctional RF Remote Control for Ultralow Standby Power Home Appliances. (26th May 2014) - Hwang, Kwang-il; Yoon, Sung-Hyun
Abstract : In spite of many benefits, since a target RF should be able to react to real time user commands even during system power-off, RF remote controls generally require more standby energy than IR manner. Therefore, in this paper a multifunctional RF remote control (MRRC), which is capable of providing larger coverage and various services, is introduced, and an ultralow standby power operation method for target RFs, utilizing an extended preamble transmission and a variable length periodic preamble sensing according to system power states, is proposed. In addition, a prototype and implementation details are also described. In order to evaluate the proposed MRRC, several experiments are conducted, and each performance of MRRC is also compared with ZigBee RF4CE no power saving and power saving mode. The experimental results demonstrate that the MRRC system enables not only ultralow standby power operation during system power-off but also low power operation even in system power-on state. In spite of ultralow standby power operation, the experimental result also shows that the MRRC provides reasonable response time to user command.